Surfactant and mechanical ventilation - Lista, G.; Castoldi, F.; Bianchi, et al., S. (Acta Biomedica Atenei Parmensis, 2012)
Even if non invasive respiratory support is widespread used in the management of respiratory failure, nevertheless mechanical ventilation and surfactant replacement are standard care for many preterm infants with respiratory distress syndrome (RDS). The interaction between exogenous surfactant and different modalities of ventilatory support are very important and can influence respiratory outcome.The optimization of surfactant replacement during respiratory support is crucial for the successful of this therapy. In course of mechanical ventilation lung recruitment manoeuvres before and after tracheal instillation of surfactant seem to facilitate its distribution and allow to obtain a more homogeneous lung volume.